What is a great work place? : a case study for Educations.com Media Group - Pekkala, Heini (2017)
This research was composed as a case study for Educations.com Media Group (EMG). The company consists of Studentum AB and FindCourses Global. Educations.com Media Group is the market leader of education marketing in Northern Europe. The company is based in Sweden and has its headquarters in the heart of Stockholm. At the time when this research was carried out, EMG operated in seven different countries. The company is expanding its operations continuously.